Bax- or Bak-Induced Mitochondrial Fission Can Be Uncoupled from Cytochrome c Release - Sheridan, Clare; Delivani, Petrina; Cullen, Sean P.; Martin, Seamus J. (Molecular cell, 2008)
Bax and Bak promote apoptosis by perturbing the permeability of the mitochondrial outer membrane and facilitating the release of cytochrome c by a mechanism that is still poorly defined. During apoptosis, Bax and Bak also promote fragmentation of the mitochondrial network, possibly by activating the mitochondrial fission machinery. It has been proposed that Bax/Bak-induced mitochondrial fission may be required for release of cytochrome c from the mitochondrial intermembrane space, although this has been a subject of debate. Here we show that Bcl-xL, as well as other members of the apoptosis-inhibitory subset of the Bcl-2 family, antagonized Bax and/or Bak-induced cytochrome c release but failed to block mitochondrial fragmentation associated with Bax/Bak activation. These data suggest that Bax/Bak-initiated remodeling of mitochondrial networks and cytochrome c release are separable events and that Bcl-2 family proteins can influence mitochondrial fission-fusion dynamics independent of apoptosis.